2023
DOI: 10.1523/jneurosci.0242-23.2023
|View full text |Cite
|
Sign up to set email alerts
|

Pupil Dilation and Microsaccades Provide Complementary Insights into the Dynamics of Arousal and Instantaneous Attention during Effortful Listening

Abstract: Listening in noisy environments requires effort – the active engagement of attention and other cognitive abilities, as well as increased arousal. The ability to separately quantify the contribution of these components is key to understanding the dynamics of effort and how it may change across listening situations and in certain populations. We concurrently measured two types of ocular data in young participants (both sexes) - Pupil dilation (PD) (thought to index arousal aspects of effort) and Microsaccades (M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…The pattern of gaze dispersion for the difficult SNR is consistent with the idea that eye movements are responsive to changes in effort. Gaze dispersion was reduced in the difficult condition, relative to the easy condition (Contadini-Wright et al, 2023; Cui & Herrmann, 2023), and then increased to similar levels as in the easy condition after sentence offset (Figures 2, 3, and 5). Yet, the continued reduction in gaze dispersion for the impossible condition suggests that eye movements may also be responsive to other aspects of cognition, such as monitoring.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…The pattern of gaze dispersion for the difficult SNR is consistent with the idea that eye movements are responsive to changes in effort. Gaze dispersion was reduced in the difficult condition, relative to the easy condition (Contadini-Wright et al, 2023; Cui & Herrmann, 2023), and then increased to similar levels as in the easy condition after sentence offset (Figures 2, 3, and 5). Yet, the continued reduction in gaze dispersion for the impossible condition suggests that eye movements may also be responsive to other aspects of cognition, such as monitoring.…”
Section: Discussionmentioning
confidence: 82%
“…Recent works suggest that reductions in eye movements may index effort. Eye movements decrease when individuals perform a high-load compared to a low-load memory task (Hutton & Tegally, 2005; Kosch et al, 2018; Lipton, Frost, & Holzman, 1980; Walter & Bex, 2021) and when speech masking increases (Contadini-Wright et al, 2023; Cui & Herrmann, 2023). We also found that gaze dispersion decreased with decreasing SNR (Figures 2, 4, and 5), and extend this previous work by showing that the sensitivity of eye movements to changes in speech masking does not differ between younger and older adults.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations